Evaluation Of Expression Patterns Of Cytokeratin And Mucin Peptide Core Antigen For Diagnostic Role In Upper Gastrointestinal Tract Pre Neoplastic And Neoplastic Lesions - Dixit, Mallika; Sharma, Shruti; Jairajpuri, Zeeba Shamim; Kapur, Sujala; Agrawal, Usha; Jain, Neelima; Thakur, Manisha; Tripathi, B.K (Annals of Pathology and Laboratory Medicine, 2018)
Introduction: Gastrointestinal tract (GIT) lesions include a wide variety of lesions, which may be diagnostically challenging on histopathology and may be difficult to differentiate without the aid of immunohistochemical stains. Objective: The present study was undertaken to histopathologically analyze the upper GIT lesions and determine the expression pattern of cytokeratin (CK) and mucin peptide core antigen (MUC) in these lesions and their usefulness in diagnosis. Material and Methods: A 135 cases with clinical diagnosis of upper GIT lesions including Barrett’s metaplasia (BM), carcinoma esophagus, gastric intestinal metaplasia (GIM) and gastric carcinoma were included. Standard diagnostic criteria were used in evaluating tissue sections and arriving at a diagnosis. Relevant clinical data including age, gender, complications and symptoms of disease were noted. Immunohistochemical evaluation of the lesions were done. The antibody panel included CK7, CK18, CK19, CK20, MUC1&MUC2. Results: Immunohistochemical pattern CK7-/CK20+ was seen in 85% gastric adenocarcinoma and 82% gastric intestinal metaplasia. CK7+/CK20- was characteristic of esophageal adenocarcinoma. CK7+/CK20+ pattern was characteristic of Barrett’s metaplasia. MUC1 and MUC2 expression was seen in both goblet and non goblet cells in Barrett’s metaplasia, MUC1 in both gastric intestinal metaplasia and MUC2 in only goblet cells. MUC2 is a good marker of mucinous carcinomas of esophagus and stomach. Conclusions: Pre-neoplastic and neoplastic lesions of the gastrointestinal tract are varied yet histologically challenging, often prove to be a diagnostic dilemma. Understanding unique immunohistochemical profiles of each, combined with histopathological and endoscopic correlation greatly assists in the diagnosis and management of these lesions.